BRIDGING THE GAP: PENGUATAN LITERASI DIGITAL KELUARGA MELALUI MEDIASI ORANG TUA DAN KERANGKA 3C’S DI KOMUNITAS RUMAH BACA - Cahayani Yogaswari; Chomariyana Kartika Hesti; Muhammad Haikal; Anang Setiawan; Reja (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program (PKM) aims to strengthen family digital literacy through the introduction of parental mediation strategies based on the 3C's framework (Child, Content, Context) at the Rumah Baca Raden Mas Suryowinoto community in Yogyakarta. The phenomenon of reversed socialization among Generation Alpha places parents in a vulnerable position due to low digital self-efficacy, triggering extreme responses of either over-restriction or complete disengagement. The program employed a participatory education method involving 18 mothers aged 38–55 years. Effectiveness was measured using pre-test and post-test instruments comprising five multiple-choice questions. Results showed an increase in average scores from 47 to 89 (scale of 100), indicating improved participant understanding of dialogue-based mediation and greater parental confidence as digital mediators. The 3C's framework proved effective as a practical guide for family mediation, integrating technical competence, psychological readiness, and the quality of parent-child communication.